A rare case of a volvulus of the ascending colon strangulated through the foramen of Winslow: “A case report and comprehensive literature review of this rare entity” - Tom Vandaele, MD; Noor Beneens, BSc; Marie De Ryck, BSc; Bart Devos, MD; Marc Philippe, MD; Mathieu Vandeputte, MD; Jo Vlasselaers, MD (Radiology Case Reports)
A herniation and strangulation of an ascending colon volvulus through the Foramen of Winslow (FoW) is an exceptionally rare surgical emergency associated with significant mortality and morbidity if not treated promptly. Obtaining a preoperative diagnosis of a Foramen of Winslow hernia (FoW-H) is challenging because of its non-specific clinical presentation, and even with advanced CT imaging the diagnosis is often missed, due to its rarity and the unfamiliarity of surgeons and radiologists with its diagnostic signs. This often leads to missed or delayed diagnoses. In this case report we presents our firsthand experience with this rare type of internal hernia. Furthermore, we provide a review of the literature on this rare pathology in which we discuss relevant signs, symptoms, risk factors, imaging signs, and treatment options. This report highlights the need for awareness for this rare disease and its clinical and radiological signs, and emphasizes the importance of an early diagnosis and timely surgical intervention to improve patient outcomes.